Preferences, perception of readiness and satisfaction towards online distance learning among undergraduates in Malaysia during COVID-19 pandemic - Sumaiyah Mat; Amyra Mohamad Yusop; Fatin Nasuha Saharudin; Leong, Vern Chin; Lim, Pei Sean; Nurul Batrisyia Omar; Tan, Weoi Peng; Tay, Ming Xin; Nor Azlin Mohd Nordin; Normala Mesbah; Deepashini Harithasan; Nor Azura Azmi; et al. (Penerbit Universiti Kebangsaan Malaysia, 2021)
While there is abundance of studies regarding online distance learning (ODL) among university students, information regarding ODL among undergraduates in Malaysia is limited, more so during the Covid-19 pandemic. This was a cross-sectional online survey involving a total of 308 undergraduates from various universities in Malaysia aimed to evaluate undergraduates’ perception of readiness and satisfaction towards online distance learning, platform preferences, attitudes and motivations, barriers towards ODL and also factors contributing to these variables. Questionnaires that include Online Learning Readiness Scale (OLRS) and additional information regarding challenges faced by undergraduates and their satisfaction levels towards ODL were used in this survey. The results showed that the undergraduates preferred a combination of face-to-face and online learning (68.8%) rather than online learning alone (5.5%). Majority of the respondents preferred having synchronous classes as compared to asynchronous classes (37.7%) and they rated Google Meet as their most preferred platform for their classes. In addition, the undergraduates shown fairly goodperception and neutral satisfaction towards ODL. Factors such as ethnicity and the state where the undergraduates lived were found to more likely cause them to have poor satisfaction towards ODL. While, undergraduates who have handphones have a higher satisfaction level towards ODL. Several challenges were encountered throughout ODL with the most challenging was the unsupportive environment, which in turn causing the undergraduates to be distracted and losing focus during ODL. Our findings highlighted that majority undergraduates preferred a combination of face-to-face and online learning rather than online learning alone. These findings will be beneficial for educators in the planning for future teaching and learning methods. Future studies with a larger sample size are needed to evaluate the independent risk factors related to low motivations, perceptions and satisfaction among undergraduates using ODL.